Relocating to retirement living: An occupational perspective on successful transitions - Walker, Emily; McNamara, Beverley (Wiley-Blackwell Publishing Asia, 2013)
Background/aim: Older adults are increasingly relocating to alternative housing options, such as retirement villages. Relocations can be stressful and these environmental transitions can cause significant disruption to the person-environment and occupational fit, thus influencing health, well-being and quality of life. There is a lack of literature from an occupational therapy perspective in relation to healthy older adults seeking to relocate. This study aimed to identify issues healthy older adults face when relocating to retirement living, what strategies they used during this process, how they maintained a sense of home, and the potential for occupational therapy involvement. Methods: Sixteen semi-structured, in-depth interviews were conducted with participants recruited from retirement living facilities across three stages of relocation; ‘Decision’, ‘Early Days’, and ‘Established’. A grounded theory approach was used to code and analyse the data. Results: Having control over the decisions surrounding relocation, being proactive rather than reactive and preparing sufficiently for the move all contributed to a positive post-location adjustment. Four main themes emerged from the narratives: timing of decision making, new beginnings, continuity, and strategies for change. Conclusions: This study contributes to literature surrounding how older adults occupy and make meaning of the spaces they call home and also enriches literature regarding environmental transitions. Relocation can be a disruptive process and occupational therapists are uniquely placed to facilitate healthy ageing throughout this transition using preventative and community-based occupational therapy.